SAT0302 Does MRI Have an Added Value over CK in Assessing Disease Activity in the Idiopathic Inflammatory Myopathies?. (10th June 2014) - Notarnicola, A.; Iannone, F.; Giannini, M.; Paolotti, S.; Scardapane, A.; Salvarani, C.; Pipitone, N.
Abstract : Background: MRI is the most widely used imaging procedure to assess disease activity of the idiopathic inflammatory Myopathies (IIM). Thigh muscle oedema, detected by T2-weighted and fat-suppressed (short tau inversion recovery, STIR) sequences, reflects active inflammation in 89-98% of IIM patients 1–2 .Despite its high sensitivity in visualizing biopsy-proven inflammatory muscle lesions, the real usefulness of MRI in evaluating myositis disease activity is still controversial 3–4 Objectives: To assess the concordance between creatine-phosphokinase (CK) levels and MRI oedema of thigh muscles in a cohort of patients with IIM. Methods: We enrolled in 2 Italian Rheumatology centers 44 IIM patients, 19 with Polymyositis (PM) and 25 with Dermatomyositis (DM) according to Bohan and Peter criteria. In all patients, CK levels (n.v. 60-190 U/L) were measured and STIR MRI sequences were acquired at the same time. MRI oedema (1= present, 0= absent) was assessed bilaterally by STIR in 17 thigh and pelvic floor muscles. A MR global oedema score (0-17) was calculated by adding the separate scores bilaterally and dividing them by two. Results: At baseline, 18 patients (41%) showed positive MRI and positive CK, 5 (11%) negative MRI and negative CK, 14 (32%) positive MRI and negative CK, and 7 (16%) negative MRI and positive CK. CK levels were in the normal range in 5 out of 19 PM patients (26%) and in 14 out of 25 DM patients (56%). The presence of oedema was detected in 11 out of 19 PM patients (56%) and in 21 out of 25 DM patients (84%). Considering the two subsets separately, the combination of negative CK and positive MRI was observed in 2 PM (11%) and in 12 DM (48%) patients. The CK-MRI concordance/discordance rate was 1.7 for PM and 0.78 for DM patients. Conclusions: At the first evaluation 32% of IIM patients (5% PM and 27% DM) had active inflammation (MRI oedema) despite normal CK levels. MRI muscle oedema was observed more frequently in DM (84%) than PM (56%) patients. Therefore, our preliminary data suggest that MRI may be considered a useful tool for disease activity assessment of IIM, especially in DM. Further studies of larger cohort of IIM patients are needed to confirm our results and evaluate the role of MRI in monitoring the disease course. References: Reimers CD, Schedel H, Fleckenstein JL, Nägele M, Witt TN, Pongratz DE, Vogl TJ. Magnetic resonance imaging of skeletal muscles in idiopathic inflammatory myopathies of adults. J Neurol 1994; 241:306-14. Fraser DD, Frank JA, Dalakas M, Miller FW, Hicks JE, Plotz P: Magnetic resonance imaging in the idiopathic inflammatory myopathies. J Rheumatol 1991; 18(11):1693-700. Tomasová Studynková J, Charvát F, Jarosová K, Vencovsky J. The role of MRI in the assessment of polymyositis and dermatomyositis. Rheumatology 2007; 46:11. A. Notarnicola, A. Scardapane, N. Pipitone, G. Zuccoli, G. Levrini, C. Salvarani, A. Marbini, A. Amati, M. Ficco, G. Angelelli, F. Iannone, G. Lapadula. The role of magneting resonance imaging (MRI) in the aassessment of idiophatic inflammatory myopathies (IIM). Ann Rheum Dis 2011;70(Suppl3):474. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5064